PEMANFAATAN ANTIOKSIDAN ALAMI FLAVONOL UNTUK MENCEGAH PROSES KETENGIKAN MINYAK KELAPA - Siswati, Nana Dyah; SU, Juni; ., Junaini (REKAPANGAN, 2010)
The rancidity that leads the quality decreasing of palm oil can be happened during theÂ storing. This unfavorable process can be controlled by using the antioxidant. In this researchÂ the skin of red onion containing flavonol was being used as the natural antioxidant to preventÂ the rancidity of the palm oil. The first step is Â extracting the flavonol from the skin of red onionÂ by using water as the dissolvent for 1 â 2,5 hours. The extract was mixed into the palm oil onÂ the Â concentration Â range Â of Â 3 â 11 Â %. Â The Â next Â step Â is Â heated Â on Â the Â humid Â temperature Â toÂ accelerate Â the Â rancidity. Â The Â mix Â of Â palm Â oil Â and Â red Â onion Â skin Â was Â being Â stored Â for Â 1 â 4Â days. The research result was detected by the level of oil peroxide. This number was showingÂ the Â level Â of Â deterioration Â of Â the Â fat Â or Â oil Â indicating Â that Â there Â was Â rancidity. Â The Â best Â resultÂ was on 11 % extracting concentration of the red onion skin, 1,5 hours extracting time, 4 daysÂ storing time of the palm oil and peroxide level of 0,6144 ( SH â 92 = 1 mg O/100 g ). Â Â _____________________________________________________________________Key word : Peroxide level, rancidity, antioxidant, skin of red onion.